Sambucus ebulus L.: Past, Present and Future - Kaya, Yilmaz; Haji, Esmael Kelil; Arvas, Yunus Emre; Aksoy, Hasan Murat (AMER INST PHYSICS, 2019)
Sambucus ebulus L. is used in local folk medicine to treat several diseases in Europe and West Asia. The objective of the review is to evaluate the S. ebulus L. in terms of past, current and future perspective. Various parts of the plant have been long used in traditional medicine for food, medicinal and ornamental purpose. Until recently, however, substantial scientific research concerning its properties has been lacking. Here, we evaluated the state of past and current scientific research concerning the use of the plant extract and related products, particularly in the treatment of antimicrobial activity. S. ebulus L. has a very high invitro antioxidant activity and no mutagenic effects at low concentrations, which makes it recommendable for applications in the food industry and pharmacology. Future studies will focus on the use of S. ebulus L. in the food and pharmaceutical industry.
Keywords: RIBOSOME-INACTIVATING PROTEINS; STAPHYLOCOCCUS-AUREUS; CLINICAL PROPERTIES; IN-VITRO; PLANTS; ANTIOXIDANT; ANTIBACTERIAL; PHARMACOLOGY; INHIBITORS; TOXICITY; Life Sciences & Biomedicine - Other Topics; Engineering